2015
DOI: 10.1590/s0102-865020150060000001
|View full text |Cite
|
Sign up to set email alerts
|

Polypropylene and polypropylene/polyglecaprone (Ultrapro(r)) meshes in the repair of incisional hernia in rats

Abstract: PURPOSE:To compare the inflammatory response of three different meshes on abdominal hernia repair in an experimental model of incisional hernia. METHODS:Median fascial incision and skin synthesis was performed on 30 Wistar rats. After 21 days, abdominal hernia developed was corrected as follows: 1) No mesh; 2) Polypropylene mesh; and, 3) Ultrapro ® mesh. After 21 days, the mesh and surrounding tissue were submitted to macroscopic (presence of adhesions, mesh retraction), microscopic analysis to identify and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
1
13
0
1
Order By: Relevance
“…In the United States, incisional hernia is the most common surgical complication 2,3 . Treatment options are fascial repair with tissue reapproximation and suture, or repair with the use of surgical mesh, implemented by Usher in 1958 4,5 .…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United States, incisional hernia is the most common surgical complication 2,3 . Treatment options are fascial repair with tissue reapproximation and suture, or repair with the use of surgical mesh, implemented by Usher in 1958 4,5 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…Utiyama et al 3 concluded that Ultrapro® and polypropylene have similar results concerning the inflammatory response, adhesion formation, mesh contraction, and complications in rats, with extraperitoneal use.…”
mentioning
confidence: 99%
“…However, they reported no reduction with porcine dermis and polypropylene (SPARC) when compared with other mesh materials. Utiyama et al (10) reported similar collapse rates for polypropylene (high density) and UltraPro (low density) in a rat hernia repair model. In our study, we observed no statistical reduction in postoperative shrinkage rates for all mesh groups when compared with preoperative baseline rates.…”
Section: Discussionmentioning
confidence: 87%
“…However, there was reportedly an increased rate of adhesions in tissue after use of polypropylene mesh materials (15,16). Utiyama et al (10) reported that polypropylene (high density) and UltraPro (low density) showed the same results for inflammatory reactions, shrinkage rate, adhesions, and complication rates in a rat hernia repair model. Yildirim et al (17) reported that use of tension-free vaginal tape (TVT, polypropylene monoflament, 75 um), intravaginal slingplasty (IVS, polypropylene Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation